Role of plasma-rich fibrin in oral surgery - K Retna Kumar; K Genmorgan; S M Abdul Rahman; M Alaguvel Rajan; T Arul Kumar; V Srinivas Prasad (Wolters Kluwer Medknow Publications, 2016)
Platelet-rich fibrin (PRF) is a fibrin meshwork, in which platelet cytokines, growth factors, and cells are entrapped and discharged after a period and can serve as a resorbable film. PRF is the next generation of platelet concentrates equipped to improve arrangement without biochemical blood handling; PRF is an evolution of the fibrin adhesive, which is widely used in the oral surgery. The guidelines of this innovation depend on concentrating platelets and growth factors in a plasma medium, and initiating them in a fibrin gel, keeping in mind the end goal to enhance the healing of wounds. Maxillary bone loss requires numerous regenerative techniques: as a supplement to the procedures of tissue regeneration, a platelet concentrate called PRF was tested for the 1st time in France by Dr. Choukroun. This article enriches the benefits and role of plasma-rich fibrin in oral surgery. Platelet-concentrate fibrin is an evolution of the fibrin glue, which is widely used in the oral surgery.